2020
DOI: 10.21203/rs.3.rs-21931/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trends in breast cancer incidence in Ho Chi Minh City 1996 - 2015:  a registry-based study

Abstract: Background and Aims: The burden of breast cancer in Vietnam has not been documented. This study sought to estimate the incidence of breast cancer in Ho Chi Minh City, the largest economic center of Vietnam, from 1996 to 2015.Methods: This was a population-based study using the Ho Chi Minh City Cancer Registry as a source of data (coverage period: 1996 - 2015). The Registry adopted the International Classification of Diseases for Oncology, 3rd Edition for the classification of primary sites and morphology, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…During botanical field surveys in Hon Ba Nature Reserve, Khanh Hoa Province, southern Vietnam in 2017, a species of Tacca was collected. After thorough examination of the Tacca species in Drenth (1972, 1976), Ding and Larsen (2000), Pham (2000), Vo (2007) and Zhang et al (2005, 2006), re-examination of specimens deposited in the Vietnamese herbaria VNM, HN and VNMN, as well as specimen images on the website of JSTOR Global Plants, P and K, we concluded that our sample belongs to a new species, which we describe in this study.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…During botanical field surveys in Hon Ba Nature Reserve, Khanh Hoa Province, southern Vietnam in 2017, a species of Tacca was collected. After thorough examination of the Tacca species in Drenth (1972, 1976), Ding and Larsen (2000), Pham (2000), Vo (2007) and Zhang et al (2005, 2006), re-examination of specimens deposited in the Vietnamese herbaria VNM, HN and VNMN, as well as specimen images on the website of JSTOR Global Plants, P and K, we concluded that our sample belongs to a new species, which we describe in this study.…”
Section: Introductionmentioning
confidence: 65%
“…Currently, six species of the genus Tacca have been recorded in Vietnam: T.chantrieri André, T.integrifolia Ker Gawl., T.leontopetaloides (L.) Kuntze, T.palmate Blume, T.plantaginea (Hance) Drenth and T.subflabellata P.P. Ling & C.Ting (Pham 2000, Vo 2007).…”
Section: Introductionmentioning
confidence: 99%
“… Asplenium wrightii was also documented in Vietnam ( Pham 1999 ; Lin and Viane 2013 ). However, we checked specimens identified as A.…”
Section: Resultsmentioning
confidence: 98%
“…Extensive field investigation and careful examination of specimens of Asplenium wrightii complex from 21 herbaria (CDBI, CSH, CZH, GH, GXMG, GZTM, HGAS, HUST, HZ, IBK, IBSC, IMC, JIU, JJF, L, MO, NAS, NA, NY, PE and SYS; abbreviations follow Thiers in Index Herbariorum available at http://sweetgum.nybg.org/science/ih/ ) and our own collections, as well as the study of protologues and other related literature( Lin and Viane 2013 ; Pham 1999 ) were carried out.…”
Section: Methodsmentioning
confidence: 99%
“…Based on further comparison with all the previously published species in Begonia sect. Sphenanthera ( Smith et al 1986 ; Ku et al 1997; Pham1999 ; Huang and Shui 2006 ; Hughes 2008 ; Averyanov and Nguyen 2012 ), its two-petalled female flower and the serpentinous adaxial leaf surface are distinct and unique in this section.…”
Section: Introductionmentioning
confidence: 85%